Effectiveness of Slow Deep Breathing Therapy Against Emesis Gravidarum - Permatasari, Ineke; Nuraini, Lutfi (Jurnal Ilmiah Kesehatan Rustida, 2024)
Emesis gravidarum is a normal symptom experienced by most pregnant women. This condition is common in early pregnancy, especially in the first week to the third month of pregnancy. The aim of this research is to find out how effective slow deep breathing therapy is for pregnant women with emesis gravidarum, quantitative research using experimental methods, using a quasi research design. experiment with a One Group Pretest-Posttest Design research design, the population in this study were all pregnant women in the Independent Practice Midwives in the Glenmore Region in 2023, totaling 30 respondents, with a classification of respondents based on age who experienced emesis gravidarum, most of whom were 25-33 years old, namely 19 respondents (63.30), most of whom had completed high school, namely 20 respondents (66.70%), most of whom worked as housewives, namely 24 respondents (80.00%). Frequency distribution of levels of nausea and vomiting before implementing slow deep breathing therapy at BPM Puspitarini, A.Md. Keb Glenmore Banyuwangi, namely 16 (53.30%) respondents with mild nausea and vomiting criteria and 14 (46.70%) respondents with nausea criteria moderate vomiting.The pre-test and post-test showed a significant relationship with p value = 0 <0.05 N = 30 It can be concluded that there is an effect of applying slow deep breathing therapy (independent) on pregnant women with emesis gravidarum.